361. A Case Control Study of COVID-19 Outcome in Patients with HIV. (31st December 2020) - Atallah, Liana; Chan, Kok Hoe; Natali, Kayla M; Nagarakanti, Sindhu; Slim, Jihad
Abstract: Background: Little is known regarding outcome of patients living with HIV (PLWH) when they get admitted to a hospital for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection. We decided to conduct a case-controlled study to try to answer the question if PLWH are at higher risk of mortality compared to individuals without HIV infection but with the same risk factors that affects outcome in COVID-19 disease. Methods: A retrospective case matched control study was performed from 03/15/2020 to 05/15/2020. We reviewed all confirmed SARS-CoV-2 infected patients who were admitted to our hospital during the study period and retrieved 7 variables: Age, gender, diabetes mellitus (DM), hypertension (HTN), body mass index (BMI), chronic kidney disease (CKD), HIV status. We divided the age in 3 groups (< 30, 30 to 60, > 60), we defined the presence of DM and HTN by reviewing the admission medications, BMI > 30 defined obesity, and CKD was present if eGFR < 45 ml/min prior to the current admission. We found 12 PLWH, we matched them for the 6 variables, we found 94 controls. The primary endpoint was percentage of inpatient mortality. Results: Of the 436 confirmed SARS-CoV-2 infection admitted between 03/15/20 and 05/15/20, 36 were still hospitalized. Twelve were PLWH out of the 400 patients with known outcome; 7 patients (58%) have the age range between 30 to 60 years old while the rest (42%) have age > 60 years old. Male to female ratio was 1:1 (6 patients each). Comorbidities were present in 10 patients (83%) with HTN (83%) being the most common, followed by CKD (58%), obesity (33%), and DM (33%). Only 1 patient expired out of the 12 PLWH (8%) admitted with COVID-19, as compared to 26 patients from the 98 matched cohort (27%) (z-score 1.38, p=0.17; odds ratio [OR], 3.972; 95% confidence interval [CI], 0.62–44.37). Conclusion: Our study suggests that PLWH do not have a worse prognosis than their matched controls for the most significant comorbid conditions affecting outcome in COVID-19 disease. Further studies with a larger sample size are urgently needed to confirm this finding. Disclosures: Jihad Slim, MD, Abbvie (Speaker's Bureau)Gilead (Speaker's Bureau)Jansen (Speaker's Bureau)Merck (Speaker's Bureau)ViiV (Speaker's Bureau)